Perbandingan Metode ARIMA Box-Jenkins dengan Moving Avarage Untuk Peramalan Harga Emas - Desmi Roma Putra Lubis; Ilka Zufria (Universitas Budi Darma, 2023)
Gold is a type of investment that is starting to be popular with many people. Gold price forecasting has an important role for investors and business people in making smart investment decisions. The problem in this research is displaying the price of gold in the market which influences many factors, for example global supply and demand, fluctuating exchange rates, the global situation, and the US dollar exchange rate. And another problem that can be taken up is forecasting gold prices which change from time to time which results in potential losses for investor trading in terms of profit risk in the market. Therefore, it is necessary to create a system that can determine gold price forecasts for investors in the market. uses the Box-Jenkins ARIMA comparison method with precise Moving Average and careful analysis to forecast gold prices. The comparison method is used to determine the trend pattern of the series and provide accurate data, namely the ARIMA Box-Jenkins method, while the Moving Average method determines the movement of the average value to estimate the next value. By calculating the prediction results of the Moving Average and ARIMA, then comparing the accuracy values of ARIMA and Moving Average, we get the accuracy value of ARIMA, namely 98.74% and Moving Average, namely 97.73%. It is known that the difference is not too different, but ARIMA gets the highest accuracy. The role of the application was carried out by conducting research at the H. ST Gold Shop. Martua by collecting gold price data, after the collected data is calculated for coding then entered into an application that has been built using the Moving Average and ARIMA methods.